2017 International Conference on Rehabilitation Robotics (ICORR) 2017
DOI: 10.1109/icorr.2017.8009459
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of walking smoothness using wearable robotic system curara® for spinocerebellar degeneration patients

Abstract: This paper aimed to verify the effectiveness of the wearable robotic system "curara" for patients with spinocerebellar degeneration (SCD) by evaluating walking smoothness. The curara system supports the wearer's gait using a synchronization control method that uses a neural oscillator based on a central pattern generator network. The system reflects the motional intention by adjusting the synchronization gains. This modifies the degree of interactive coordinated motion between the curara and the wearer. As a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…With this gait assist system, patients could walk more smoothly with an increased harmonic ratio while wearing the exoskeleton compared to the gait without the exoskeleton. There were no major changes in gait speed, stride length, and cadence in most patients [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…With this gait assist system, patients could walk more smoothly with an increased harmonic ratio while wearing the exoskeleton compared to the gait without the exoskeleton. There were no major changes in gait speed, stride length, and cadence in most patients [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the over-ground RAGT with a wearable robot system has been used in the treatment of patients with spinocerebellar ataxia [ 27 , 28 ]. They found that these patients could walk more smoothly with an increased harmonic ratio while walking with the wearable robot system than without the system.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, various technologies have been used in the assessment of and treatment based on rehabilitation, as well as to support daily life in patients with SCD. Curara, a wearable robotic system, assists both hip and knee movements and supports the wearer's rhythmic gait using a synchronization control based on a central pattern generator [109]. Gait support using the curara system has been reported to improve gait smoothness in patients with SCD [110].…”
Section: Assistive Technologymentioning
confidence: 99%